High-throughput sequencing of complete human mtDNA genomes from the Philippines - Gunnarsdóttir, Ellen D.; Li, Mingkun; Bauchet, Marc; Finstermeier, Knut; Stoneking, Mark (Genome Research, 2011)
Because of the time and cost associated with Sanger sequencing of complete human mtDNA genomes, practically all evolutionary studies have screened samples first to define haplogroups and then either selected a few samples from each haplogroup, or many samples from a particular haplogroup of interest, for complete mtDNA genome sequencing. Such biased sampling precludes many analyses of interest. Here, we used high-throughput sequencing platforms to generate, rapidly and inexpensively, 109 complete mtDNA genome sequences from random samples of individuals from three Filipino groups, including one Negrito group, the Mamanwa. We obtained on average ∼55-fold coverage per sequence, with <1% missing data per sequence. Various analyses attest to the accuracy of the sequences, including comparison to sequences of the first hypervariable segment of the control region generated by Sanger sequencing; patterns of nucleotide substitution and the distribution of polymorphic sites across the genome; and the observed haplogroups. Bayesian skyline plots of population size change through time indicate similar patterns for all three Filipino groups, but sharply contrast with such plots previously constructed from biased sampling of complete mtDNA genomes, as well as with an artificially constructed sample of sequences that mimics the biased sampling. Our results clearly demonstrate that the high-throughput sequencing platforms are the methodology of choice for generating complete mtDNA genome sequences.
10.1101/gr.107615.110